Lament : the faerie queen's deception - Stiefvater, Maggie, 1981- (Flux, 2008)
On the day of an important music competition, talented but painfully introverted and nervous Deirdre Monaghan is helped to perform by the compelling and enigmatic Luke Dillon and finds herself inexorably drawn into the mysteries and dangers of the faerie world.